Predictors of smoking cessation in a cohort of adult smokers followed for five years. (1997) - Hymowitz, N; Cummings, K M; Hyland, A; Lynn, W R; Pechacek, T F; Hartwell, T D
Abstract : OBJECTIVE: To identify variables predictive of smoking cessation in a cohort of cigarette smokers followed for five years. DESIGN: Data analysed in this paper come from a cohort tracking telephone survey of 13415 cigarette smokers aged 25-64 years from 20 American and two Canadian communities who were interviewed in 1988 and re-interviewed in 1993 as part of the National Cancer Institute's Community Intervention Trial for Smoking Cessation. Predictors of smoking cessation evaluated in this study included measures of past and current smoking behaviour, past quit attempts, stated desire to quit smoking, and demographic characteristics. OUTCOME MEASURES: Smoking cessation was based on self report. A "quitter" was defined as a cohort member who, at the final annual contact in 1993, reported not smoking any cigarettes for the preceding six months or longer. Any smoker who reported having made a serious quit attempt between 1988 and 1993 was asked to indicate reasons that contributed to their decision to try to stop smoking. RESULTS: 67% of smokers reported making at least one serious attempt to stop smoking between 1988 and 1993 and, of these, 33% were classified as having quit smoking in 1993. The most common reasons given for quitting smoking were concern over health (91%), expense (60%), concern about exposing others to secondhand smoke (56%), and wanting to set a good example for others (55%). Statistically significant predictors of smoking cessation included male gender, older age, higher income, less frequent alcohol intake, lower levels of daily cigarette consumption, longer time to first cigarette in the morning, the use of premium cigarettes, initiation of smoking after age 20, history of past quit attempts, a strong desire to stop smoking, and the absence of other smokers in the household. Predictor variations with the largest relative risks for smoking cessation were those associated with nicotine dependence such as amount smoked daily and time to first cigarette in the morning. CONCLUSIONS: Despite the fact that most smokers expressed a strong desire to stop smoking in 1988, the majority, especially the most dependent heavy smokers (>25 cigarettes/day), struggled unsuccessfully to achieve this goal.